Tren dan Tantangan Pelaksanaan Distance Learning di Pendidikan Tinggi: Kajian Sistematis 2020–2024 - Nur'akbar, Tomy; Jabar, Abdul; Nisa, Vika Zakiyatun; Wicaksono, Dirgantara (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This systematic literature review aims to analyze the trends, challenges, and empirical findings of distance learning and blended learning in higher education during the period 2020–2024. Utilizing the PRISMA protocol, this study synthesizes 120 articles identified through major academic databases and narrowed down to 42 eligible studies that meet the inclusion criteria. Findings indicate three dominant trends: the massive adoption of digital learning platforms, the increasing integration of learning analytics in monitoring student engagement, and the shift from emergency remote learning toward sustainable hybrid models. However, persistent challenges remain, including digital inequality, varying levels of digital readiness among lecturers and students, inconsistent instructional quality, low student engagement, and concerns regarding data ethics in learning analytics. Results also show heterogeneous learning outcomes influenced by variations in pedagogical design, technological infrastructure, and student characteristics. This review outlines key research gaps and proposes future directions, including longitudinal studies, contextual investigations in low-resource settings, and multi-dimensional evaluations that integrate cognitive, affective, and social outcomes. The findings contribute to strengthening policy formulation and instructional design for sustainable post-pandemic higher education